Utilisation of prosody in sentence processing and communicative effectiveness among second language users: a case of Malaysian speakers / Julia Madzalan - Madzalan, Julia (2017)
This study focuses on the utilisation of prosody features, namely the pitch or intonation, stress and pause pattern in assisting comprehension of spoken interaction among users of English as second language in Malaysia. The objectives of this study are to identify the relation between prosody utilisation and communicative effectiveness among second language users in Malaysia; as well as identifying the most facilitating prosody feature in assisting comprehension. The study mainly refers to theories as proposed by Teilanyo (2010) and Gilbert (2008) and the study design refers to a model proposed by Peppe (2011). 30 respondents were involved in the pilot study and 106 respondents were involved in the main study. A quasi experimental design was adopted in the study using Pre- and Post-test design, and analysis was conducted using paired sample t-test in testing the hypotheses formed. After completion of the tests, a set of questionnaire was distributed to respondents in the experimental group for the purpose of data triangulation. It was found in this study that prosody facilitated comprehension in communication among second language users in Malaysia. Pitch or intonation pattern is found to be the most facilitating feature, followed by stress pattern and the least facilitating feature is pause pattern.